Stool microbiome reveals diverse bacterial ureases as confounders of oral urea breath testing for Helicobacter pylori and Mycobacterium tuberculosis in Bamako, Mali. (17th August 2016) - Maiga, Mamoudou; Cohen, Keira; Baya, Bocar; Srikrishna, Geetha; Siddiqui, Sophia; Sanogo, Moumine; Somboro, Anou M; Diarra, Bassirou; Diallo, Mariam H; Mazumdar, Varun; Yoder, Christian; Orsega, Susan; et al.
Abstract: Detection of bacterial urease activity has been utilized successfully to diagnose Helicobacter pylori (H. pylori) . While Mycobacterium tuberculosis ( M. tuberculosis ) also possesses an active urease, it is unknown whether detection of mycobacterial urease activity by oral urease breath test (UBT) can be exploited as a rapid point of care biomarker for tuberculosis (TB) in humans. We enrolled 34 individuals newly diagnosed with pulmonary TB and 46 healthy subjects in Bamako, Mali and performed oral UBT, mycobacterial sputum culture and H. pylori testing. Oral UBT had a sensitivity and specificity (95% CI) of 70% (46–88%) and 11% (3–26%), respectively, to diagnose culture-confirmed M. tuberculosis disease among patients without H. pylori, and 100% sensitivity (69–100%) and 11% specificity (3–26%) to diagnose H. pylori among patients without pulmonary TB. Stool microbiome analysis of controls without TB or H. pylori but with positive oral UBT detected high levels of non- H. pylori urease producing organisms, which likely explains the low specificity of oral UBT in this setting and in other reports of oral UBT studies in Africa.